The new age and conventional communication - Marco Roodt (Communicare)
kspite 14 joint years of working for two large Parastatal corporations and the largest Financial Services institution on the African continent, and of late three years as an independent communication consultant, I still have no clear-cut answer to the question of what the future holds for conventional communication. Note that I am steering clear of the word communications. Communications would in my view be referring to those information-technology-trained experts driving luxury cars at an age when they had barely qualified for a legal driver's licence, or to the richest person in the world who has, by starting a dot.com business, surpassed in stock wealth the software wunderkid of the eighties. They are indeed also part and parcel of communication. The only thing is that they seem to be successful on a large scale where people electing to qualify and practise in the field of conventional communication appear to have much less to be happy about. This statement would probably further demoralise current students of communication, academia, starter-up practitioners, those who are in fact making it and let us not forget communication advisers. The question is are we making it professionally or are we practising an unnecessary art and science? Let us, explore this issue by looking objectively at some pertinent communication industry (not IT) mind teasers, turning them into statements and then arguing the realities surrounding them.